Combination of Chemotherapy and Mild Hyperthermia Using Targeted Nanoparticles: A Potential Treatment Modality for Breast Cancer - Ishdeep Kaur; Terence Tieu; Veerasikku G. Deepagan; Muhammad A. Ali; Fahad Alsunaydih; David Rudd; Maliheh A. Moghaddam; Laure Bourgeois; Timothy E. Adams; Kristofer J. Thurecht; Mehmet Yuce; Anna Cifuentes-Rius; et al. (MDPI AG, 2023)
Despite the clinical benefits that chemotherapeutics has had on the treatment of breast cancer, drug resistance remains one of the main obstacles to curative cancer therapy. Nanomedicines allow therapeutics to be more targeted and effective, resulting in enhanced treatment success, reduced side effects, and the possibility of minimising drug resistance by the co-delivery of therapeutic agents. Porous silicon nanoparticles (pSiNPs) have been established as efficient vectors for drug delivery. Their high surface area makes them an ideal carrier for the administration of multiple therapeutics, providing the means to apply multiple attacks to the tumour. Moreover, immobilising targeting ligands on the pSiNP surface helps direct them selectively to cancer cells, thereby reducing harm to normal tissues. Here, we engineered breast cancer-targeted pSiNPs co-loaded with an anticancer drug and gold nanoclusters (AuNCs). AuNCs have the capacity to induce hyperthermia when exposed to a radiofrequency field. Using monolayer and 3D cell cultures, we demonstrate that the cell-killing efficacy of combined hyperthermia and chemotherapy via targeted pSiNPs is 1.5-fold higher than applying monotherapy and 3.5-fold higher compared to using a nontargeted system with combined therapeutics. The results not only demonstrate targeted pSiNPs as a successful nanocarrier for combination therapy but also confirm it as a versatile platform with the potential to be used for personalised medicine.